2018
DOI: 10.4088/jcp.17m11597
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and Improvement of Depression Following Electroconvulsive Therapy in Treatment-Resistant Depression

Abstract: Objective Electroconvulsive therapy (ECT) is the most robust acute treatment for severe major depressive disorder, yet clinical response is variable. Inflammation is associated with depression, especially in women, and levels of C-reactive protein (CRP) and interleukin-6 (IL-6) predict response to antidepressant medications. This study evaluated whether markers of inflammation predicted response to electroconvulsive therapy (ECT) in patients with treatment resistant depression, and to what extent this associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
60
2
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(75 citation statements)
references
References 41 publications
3
60
2
5
Order By: Relevance
“…However, the baseline IL-6 levels decreased among remitters after repeated ECT treatment. The findings are replicated by the following study and further demonstrated that IL-6 levels prior to ECT treatment may be a useful marker in identifying those MDD patients most likely to respond to ECT treatment [120].…”
Section: Electroconvulsive Therapymentioning
confidence: 57%
“…However, the baseline IL-6 levels decreased among remitters after repeated ECT treatment. The findings are replicated by the following study and further demonstrated that IL-6 levels prior to ECT treatment may be a useful marker in identifying those MDD patients most likely to respond to ECT treatment [120].…”
Section: Electroconvulsive Therapymentioning
confidence: 57%
“…Some depressed patients show elevated levels of systemic inflammatory markers [7], along with increased expression of inflammationrelated genes in monocytes or peripheral blood mononuclear cells [8,9]. Moreover, among the substantial minority (i.e., about 30%) of patients with elevated levels of inflammation [10], treatment response varies along with inflammation [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Lower promoter methylation rates of BDNF exon I were strictly associated with remission (Kleimann et al, 2015), and the CC genotype of BDNF polymorphism C270T contributed a useful response (Huuhka et al, 2007). In support of inflammation, higher levels of IL-6 at baseline anticipated profound depression relief, especially in females (Kruse et al, 2018), and the degree of change in serum matrix metalloproteinase-9 (MM-9) was associated with relapse following ECT (Shibasaki et al, 2018).…”
Section: Prediction Of Response and Relapse To Ect Bioinformaticsmentioning
confidence: 98%
“…In short, in the elderly (Husain et al, 2004), psychotic symptom comorbidities (Husain et al, 2004), postpartum depression (Rundgren et al, 2018), shorter episode duration and more severe depressive symptoms (van Diermen et al, 2018), early depression alleviation (Birkenhager et al, 2019), lower NAA levels in the dACC at baseline (Njau et al, 2017), low genetic risk load (Foo et al, 2019), genetic or epigenetic modifications (Huuhka et al, 2007;Kleimann et al, 2015;Lin et al, 2015), and high baseline serum IL-6 levels (Kruse et al, 2018) and a serum MM-9 profile (Shibasaki et al, 2018) were more likely to benefit ECT recipients. Moreover, the subfield index of hippocampus and neural network plasticity (Abbott et al, 2014;Ota et al, 2015;van Waarde et al, 2015;Redlich et al, 2016;Cao et al, 2018;Nuninga et al, 2019) may provide precise evidence to predict the outcome.…”
Section: Prediction Of Response and Relapse To Ect Bioinformaticsmentioning
confidence: 99%